PRELIMINARY DATA FROM THE FIRST RECORD OF THE EARLY TOARCIAN OCEANIC ANOXIC EVENT IN THE SEDIMENTS OF THE PINDOS ZONE (GREECE) - Kafousia N., Kafousia N.; Karakitsios, V.; Jenkyns, H.C. (Bulletin of the Geological Society of Greece, 2010)
The Early Toarcian Oceanic Anoxic Event (ca 183 Ma) coincides with high palaeotemperatures, regional anoxia to euxinia, marine transgression, mass extinction and high rates of organic-carbon burial in a global context. Most of the detailed studies of this event have investigated deposits formed in the epicontinental seas of northern Europe, although coeval organic-rich shales are known locally in the Tethyan region. However, the global or regional character of this event is still under debate. In this study we present, for the first time, a high-resolution geochemical record of the Early Toarcian Oceanic Anoxic event in pelagic sediments (Kastelli Pelites) formed in a long-lived Mesozoic deep-sea basin, corresponding to the western passive margin of the Pindos Ocean of western Greece. Our data record both the positive excursion in total organic carbon (TOC) and the characteristic negative excursion in δ13Ccarb. The δ13Ccarb values are very stable in the bottom of the section ( 2‰), whereas higher in the section the values drop down to -5‰. Following this negative excursion, the carbonate carbon-isotope ratios return to background values. The TOC excursion is modest, rising from a background of 0.05% to 2% and then returning to a background of 0.04%. Because both relative enrichment in TOC and the negative carbon-isotope excursion that characterize the Toarcian OAE are recorded in some of the deepest marine sediments of the Tethyan region, the global significance of the event is reinforced.